Teaching factory, internal quality assurance system, and vocational teacher quality culture - Agustina Sri Purnami; Mulyanto Mulyanto; Susilo Utomo (Intelektual Pustaka Media Utama, 2021)
The purpose of this study was to determine the effect of the effectiveness of the application of teaching factory learning and Internal Quality Assurance System on motivation of quality culture. This was a quantitative research which is analyzed using multiple regression. The sample used in this study were 79 teachers who were taken by purposive sampling. The instrument used to obtain data using a questionnaire. The results showed that the regression line equation with the significance test of the F test= 60.414 with a significance level of 0.00, meaning that the equation is able to predict changes in the culture of teacher quality caused by changes in variants of teaching factory and Internal Quality Assurance System. The effect of teaching factory and Internal Quality Assurance System on motivation of quality culture stated the value of R2 is 0.530. In this regard, it can be concluded that there is an influence between teaching factory and Internal Quality Assurance System on motivation of quality culture.